Biometric verification of a subject through eye movements - Juhola, Martti; Zhang, Youming; Rasku, Jyrki (Computers in biology and medicine, 2013)
Matching digital fingerprint, face or iris images, biometric verification of persons has advanced. Notwithstanding the progress, this is no easy computational task because of great numbers of complicated data. Since the 1990s, eye movements previously only applied to various tests of medicine and psychology are also studied for the purpose of computer interfaces. Such a short one-dimensional measurement signal contains less data than images and may therefore be simpler and faster to recognize. Using saccadic eye movements we developed a computational verification method to reliably distinguish a legitimate person or a subject in general from others. We tested features extracted from signals recorded from saccade eye movements. We used saccades of 19 healthy subjects and 21 otoneurological patients recorded with electro-oculography and additional 40 healthy subjects recorded with a videocamera system. Verification tests produced high accuracies.